Characterization of Soft Contact Lens Fitting Using Ultra-Long Scan Depth Optical Coherence Tomography - Lele Cui; Ming Li; Meixiao Shen; Fan Lu; Jianhua Wang (Journal of Ophthalmology)
Objectives. To evaluate the centration and movement of soft contact lenses and to verify the repeatability of two repeated measurements of the lens centration and movement using ultra-long scan depth optical coherence tomography (UL-OCT). Methods. A 1-day Acuvue® Define™ lens was tested on both eyes of 10 subjects (5 males and 5 females; mean age, 31.6 years). The centration and blink-induced movement of the contact lens were measured using UL-OCT at 5 min and 30 min after insertion. The measurements were repeated once at each checkpoint. Results. Good repeatability was found in the lens centration and movement between the two repeated measurements at either checkpoint. The values of the lens movement were 0.457 ± 0.248 mm and 0.402 ± 0.229 mm at 5 min and decreased to 0.197 ± 0.065 mm and 0.211 ± 0.110 mm at 30 min after insertion for the right and left eyes, respectively (P<0.05). Conclusions. The custom-built UL-OCT presented good repeatability of centration and movement in Define lenses at 5 min and 30 min after insertion. Most of the lenses were centered temporal and inferior to the cornea during the first 30 min wearing period. Compared with 5 min after insertion, the lens was centered better and exhibited less movement at 30 min.